Thermal behavior of cocrystal: a case study of ketoprofen-malonic acid and ketoprofen-nicotinamide cocrystals - Wicaksono, Yudi; Setyawan, Dwi; Nugraha, Ari Satia; Siswandono (Penerbit Universiti Kebangsaan Malaysia, 2020)
Thermal properties are essential parameters in transformations of solid state. It is useful for estimating physicalchemical interactions that occur specifically in a multicomponent system as cocrystal. However, there is still minimum information about determining the thermal properties of cocrystal in literature. In this study, the investigation of thermal behavior of cocrystal was determined in non-isothermal conditions based on the Kissinger method. The ketoprofen-malonic acid (KMA) and ketoprofen-nicotinamide (KN) cocrystal used as model were prepared using solvent evaporation method, while the characterization was performed by powder x-ray diffraction (PXRD), differential scanning calorimetry (DSC), and Fourier-transform infrared (FTIR). From the experimental results, the activation energy (Ea ) of pure ketoprofen, KMA cocrystal, and KN cocrystal are 264.38, 384.77, and 116.64 kJ mol-1, while the enthalpy of activation (ΔH*) are 261.31, 381.78, and 113.76 kJ mol-1, respectively. The calculated values of entropy of activation (ΔS*) for pure ketoprofen, KMA cocrystal, and KN cocrystal are 465.22, 809.77, and 84.34 J K-1 mol-1 and the free energy of activation (ΔG*) of pure ketoprofen, KMA cocrystal, and KN cocrystal obtained by general thermodynamic equation are 89.53, 90.87, and 84.62 kJ mol-1, respectively. Experimental results of the thermodynamic parameters showed cocrystals to have a positive value of ΔS*, indicating the formation of cocrystals was a nonspontaneous process. Also, the KMA cocrystal had greater free energy of activation (ΔG*) than the KN cocrystal which indicated the formation of the crystal lattice involving greater binding energy than KN cocrystal.